Analisa Laporan Keuangan dengan Perhitungan Analisis Trend (Index Number Trend Series Analisis) pada PT Timah Tbk (TINS) - Ningrum, Indah Sulistia; Hayati, Syarifatull; Nurlita, Amelia; Sarmila, Wingki; Amelia, Elda; Ramadhani, Andini; Polshia, Rasi; Fatmawati, Nurul; Armel, Raja Septian; Nurmanto, Billy (Universitas Katolik Widya Karya Malang, 2024)
This research was carried out with the aim of finding out how to calculate Trend Analysis (Index Number Series Analysis) in PT Timah Tbk financial reports and how to explain the results of calculations using Trend Analysis (Index Number Series Analysis). The research approach uses a quantitative type using secondary data collected using documentation and literature study methods. By analyzing financial report data at PT Timah Tbk. The technique for collecting secondary data is carried out using documentation techniques. namely by collecting company financial reports from December 31 2020. 2021. 2022. 2023 and March 31 2024. Data is collected from the official IDX website. namely (www.idx.co.id) by downloading . The research results show that the financial trend analysis of PT Timah Tbk from 2020 to 2024 shows significant changes in various aspects of the company's finances. PT Timah Tbk succeeded in increasing its total equity. major challenges in maintaining revenue and cost efficiency led to a decrease in overall profitability. In research. researchers have an interest in time and knowledge. which results in less comprehensive research results and obtaining limited information.